RELATED REASONS TO STUDENTS' RELUCTANCE TO ENROLL IN THE DEPARTMENT OF MANAGEMENT INFORMATION SYSTEMS MIS, BUSINESS SCHOOLS IN SAUDI UNIVERSITIES - Nabil Mohemmed Al-Hazmi (International Journal of Modern Agriculture, 2021)
This study aims at identifying the related reasons to students' reluctance to enroll in the of Information Management Systems MISdepartment at the Business School at Prince Sattam Bin Abdulaziz University due to the significance of MIS specialization. The study used the descriptive analytical method as a questionnaire was designed and distributed to the sample of the study. The study has reached several results, the most important of which are the difficulty of the courses in the department, the teaching methods of these courses are traditional and the lack and limitation of the role of academic guidance. The study has presented a set of recommendations, the most important of which was reconsidering the department's courses and their teaching methods,activating the role of academic guidance at the college and promote MISdepartment through conducting awareness and promoting programs aimed at students graduating from high schools.